Pengalaman Kader dalam Pelayanan Posyandu - Viertianingsih Patungo (Jurnal Keperawatan Silampari, 2023)
This study aims to obtain an in-depth description of the experience of Cadres in Elderly Posyandu services in Yahim Sentani Village, Jayapura Regency, Papua. The research method is qualitative research with a phenomenological approach. The results of this study show three themes, namely, carrying out the elderly posyandu, managing the elderly posyandu, and using the elderly posyandu. It was concluded that the participants in implementing the elderly Posyandu had not yet arrived at health checks such as blood pressure and had not provided counseling. In posyandu management, participants expressed their desire to take part in training and complete the posyandu infrastructure for the elderly. Keywords: Elderly, Experience of Cadres, Elderly Posyandu